Al-Tahlil al-Dilaly wa Tathbiq al-Tarbawi Lima’na Kalimah Mubarak fi al–Qur’an al-Karim ‘ala Manzhuri Toshihiko Izutsu - Mubarok, Khusnul; Hadziq, Muhammad Fadhil; Nidhomillah, Abd Rofi Fathoni (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Semantics, a branch of linguistics, studies meaning in language by analyzing how words and sentences convey meaning in the context of communication. This study aims to use a semantic approach to understand how meaning is formed and interpreted in the Qur'ān. The main objective is to analyze the meaning of the word "Mubarak" in the Qur'an using Toshihiko Izutsu's semantic method for a deeper and comprehensive understanding of the religious and cultural significance of this word. This study uses a qualitative method based on desk research, in which Qur'ānic verses containing the word "Mubarak" are analyzed using Toshihiko Izutsu's semantic analysis approach. This analysis includes a review of relevant literature and Izutsu's works to understand the historical and cultural context. The results of the study found that the word mubarak amounted to 12 words contained in different verses and surahs. The word mubarak has a different meaning in each verse and surah this is in accordance with the context of each verse, in the form of: place, book, person, water, time, and saving.